Dissociable roles of different types of working memory load in visual detection - Konstantinou, Nikos; Lavie, Nilli (My University, 2013)
We contrasted the effects of different types of working memory (WM) load on detection. Considering the sensory-recruitment hypothesis of visual short-term memory (VSTM) within load theory (e.g., Lavie, 2010) led us to predict that VSTM load would reduce visual-representation capacity, thus leading to reduced detection sensitivity during maintenance, whereas load on WM cognitive control processes would reduce priority-based control, thus leading to enhanced detection sensitivity for a low-priority stimulus. During the retention interval of a WM task, participants performed a visual-search task while also asked to detect a masked stimulus in the periphery. Loading WM cognitive control processes (with the demand to maintain a random digit order [vs. fixed in conditions of low load]) led to enhanced detection sensitivity. In contrast, loading VSTM (with the demand to maintain the color and positions of six squares [vs. one in conditions of low load]) reduced detection sensitivity, an effect comparable with that found for manipulating perceptual load in the search task. The results confirmed our predictions and established a new functional dissociation between the roles of different types of WM load in the fundamental visual perception process of detection.
Keywords: Executive cognitive control; Visual working memory; Perceptual load; Selective attention; Visual detection